Positive Psychology: Overview of the Links between Trait Emotional Intelligence and Positive Psychology - Garbenis, Simas (Vilnius University Open Series, 2020)
The main purpose of this article is to reveal the interaction between trait emotional intelligence and positive psychology ideas. The article reviews the main idea of positive psychology, examines the 3 main levels of this discipline, and their essential principles. The article also provides brief insights into different theories of emotional intelligence, focusing on the features of trait emotional intelligence, its structure and functions. Theoretical insights revealing the interactions between the ideas of positive psychology and emotional intelligence are presented not only in terms of functions of trait emotional intelligence, but also in terms of its trait structure manifestation at different levels of positive psychology. It has been established that the interaction of trait emotional intelligence and positive psychology exists due to functions of emotional intelligence, its perspectives in predicting life success and the structure of traits manifested at the subjective, individual and group levels of positive psychology.
Keywords: positive psychology; emotional intelligence; emotional intelligence theories; emotions